2003
DOI: 10.1128/jvi.77.21.11674-11684.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Inactivation of Two Distinct Negative RNA Elements in the Human Papillomavirus Type 16 L2 Coding Region Induces Production of High Levels of L2 in Human Cells

Abstract: Here we show that the 5 end and the middle region of the L2 coding sequence of human papillomavirus type 16 contain strong inhibitory RNA sequences termed inhibitory regions I and II. This is in contrast to L1, which contains one inhibitory region in the 5 end of the coding region. Inhibitory regions I and II acted in cis to reduce L2 mRNA levels and to inhibit the use of the mRNA. In tandem, the two regions reduced L2 mRNA production to undetectable levels. Specific mutational inactivation of the two inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
66
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 30 publications
1
66
0
Order By: Relevance
“…The late 39-untranslated region (39UTR) has been identified as the location of RNA regulatory elements in many HPV types, including HPV-16 (Graham, 2008;Zhao et al, 2007). RNA regulatory elements have also been identified in the L1 and L2 protein-encoding regions of HPV-16 (Collier et al, 1998(Collier et al, , 2002Oberg et al, 2003). Reports also suggest that the control of late gene expression extends to regulatory elements in the early region of HPV-16, and polyadenylation elements at the early poly(A) signal pAE may influence late gene expression .…”
Section: Introductionmentioning
confidence: 99%
“…The late 39-untranslated region (39UTR) has been identified as the location of RNA regulatory elements in many HPV types, including HPV-16 (Graham, 2008;Zhao et al, 2007). RNA regulatory elements have also been identified in the L1 and L2 protein-encoding regions of HPV-16 (Collier et al, 1998(Collier et al, , 2002Oberg et al, 2003). Reports also suggest that the control of late gene expression extends to regulatory elements in the early region of HPV-16, and polyadenylation elements at the early poly(A) signal pAE may influence late gene expression .…”
Section: Introductionmentioning
confidence: 99%
“…This primarily affected the L2 mRNA half-life (37) and translation (9). A mutant (Mut) L2 gene was generated in which the L2 RNA sequence, but not the L2 protein sequence, was altered (30). This mutant L2 gene produced high levels of L2 mRNA and L2 protein, indicating that inhibitory RNA elements in L2 had been inactivated (30).…”
mentioning
confidence: 99%
“…It was shown that these elements encoded multiple binding sites for the CStF-64 polyadenylation factor, suggesting that these RNA elements in L2 acted in concert to promote early polyadenylation in HPV-31 (43). In earlier studies, we found that the HPV-16 L2 coding region contains RNA elements that efficiently block expression of L2 from L2 cDNA expression plasmids transiently transfected into HeLa cells (9,10,30,37). This primarily affected the L2 mRNA half-life (37) and translation (9).…”
mentioning
confidence: 99%
See 2 more Smart Citations